Dampak aktivitas tambang PT. PDNI terhadap tingkat pendapatan masyarakat petambak di Desa Diolo Kecamatan Bondoala Kabupaten Konawe - Musnia; Lawelle, Sjamsu Alam; Rosmawati; Ruslaini; Mansyur, Akhmad; Patiung, Seventry Meliana; Siang, Roslindah Daeng (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to determine the impact of mining activities on the income level of the farming community and to determine the income level of the farming community before and before the operation of the mining company. This research was conducted in Diolo Village, Bondoala District, Konawe Regency, from August to September 2019. This study used a method census with a total of 20 respondents. Data obtained through interviews using questionnaires, observation, and documentation. Data were analyzed descriptively qualitatively and quantitatively using the formula for costs, revenues, and income. The results showed that the nickel mining activities of PT. Virtue Dragon Nickel Industry has a positive and negative impact on farmers. The positive impact is an increase in people's income as employees in the company. The negative impact caused by the company's activities on fishpond cultivation activities is by decreasing the amount of aquaculture production. The income earned before the presence of the mine was Rp. 14.074.798/cycle and after the existence of the mine was Rp2.521.875/cycle. this means after mining, the income of farmers has decreased